2009
DOI: 10.1136/thx.2007.086017
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of vascular endoprosthesis for malignant superior vena cava syndrome

Abstract: Background: Superior vena cava syndrome management has been traditionally radiation therapy, chemotherapy or chemoradiation, depending on the underlying malignancy involved and individual clinicopathological features of the case. Recent emergence of endovascular stents offer the opportunity for immediate relief of the venous stenosis. This review examines findings from the published series which used endovascular prosthesis for this syndrome with regards to efficacy and safety. Methods: Literature search ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 37 publications
3
59
0
6
Order By: Relevance
“…Surgical interventions with reconstruction of the superior vena cava are possible but can only be performed in few patients selected on the basis of strict criteria [17 -19]. In the last 20 years, it has been shown multiple times that endovascular stents for symptomatic therapy of superior vena cava syndrome have great potential regarding symptom control and prevention of relapse [7,20,28].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical interventions with reconstruction of the superior vena cava are possible but can only be performed in few patients selected on the basis of strict criteria [17 -19]. In the last 20 years, it has been shown multiple times that endovascular stents for symptomatic therapy of superior vena cava syndrome have great potential regarding symptom control and prevention of relapse [7,20,28].…”
Section: Discussionmentioning
confidence: 99%
“…Nguyen and colleagues found only one case of SVC rupture among the 884 cases reviewed (0.1%). 5 Other authors have reported rates of tamponade as high as 1.8%. 6 A total of 16 cases of SVC perforation and hemopericardium have been described in the literature.…”
Section: Svc Rupture and Cardiac Tamponade As A Complication Of Stentingmentioning
confidence: 95%
“…Of the 17 fatalities, 7 were caused by severe hemorrhage, 3 by respiratory events, and 4 by cardiac complications-including 1 cardiac tamponade. 5 In this initial description of SVC stenting, Charnsangavej and colleagues used Gianturco Z stents. 4 Since then, an array of stents have been used to treat SVCS, but there is a paucity of data assessing individual stent performance.…”
Section: Svc Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…39 Basically, anticoagulation is recommended after SVC stenting, which might interfere with necessary invasive diagnostic procedures if not done before, but duration and type of anticoagulation remain controversial. However, thrombolytics increased the complication rate after SVC stenting to as high as 10%.…”
Section: Endovascular Treatmentmentioning
confidence: 99%